Mechanism of the Formation, Properties and Molecular Structure of Slowly Digestible Starch from the African Locust Bean Parkia biglobosa Collected from Conakry, Guinea - Sankhon, A.; Wang, L.; Yao, W.; Amadou, I.; Wang, H.; Qian, H.; Sangare, M. (Asian Journal of Chemistry, 2013)
Slowly digestible parkia starch prepared by prehydrolysis with a-amylase and amyloglucosidase at different times (20, 45, 70, 95, and 120 min) were investigated. The in vitro Englyst test showed 52.29 % slowly digestible parkia starch content and the digestion results of the prehydrolyzed starch showed an almost constant amount of slowly digestible parkia starch, although an increase of rapidly digestible starch accompanied a reduction of resistant starch with increasing prehydrolysis time. Scanning electron microscopy revealed that slowly digestible parkia starch results from an increase of pore size until almost complete fragmentation of starch granules. Amylopectin and amylose ratio contributed to the amount of slowly digestible parkia starch at different digestion time. Prehydrolysis parkia starch with nutritional quality and functionality affected by encapsulating easily digestible material, for example, gelatinized starch. X-Ray powder between layers of SEM are resistant to enzyme digestion, thus, food products with multiple layers of this structure would likely have a slow digestion property.